UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) PADA SISWA KELAS VIII.6 SMP NEGERI 21 PEKANBARU - Wulandari, Puteri; ', Jalinus; ', Zuhri D (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the result of students math achievement at class VIII.6 SMP Negeri 21 Pekanbaru which is still under the minimum mastery criteria with a percentage of 42,5% or 17 students from 40 students who achieve the minimum mastery criteria on the subject matter of the Pythagoras Theorem and 40% or 16 students from 40 students who achieve the minimum mastery criteria on the subject matter of the Circles Tangent. This research aims to improve increase students mathematics achievement through implementation of cooperative learning type Team Games Tournament. This type of research is the Classroom Action Research with two cycle. The research was conducted in class VIII.6 SMP Negeri 21 Pekanbaru in the second semester of the 2015/2016 academic years with the subject of as many 40 students, consist of 22 boys and 18 girls. The research instrument consists of learning device s and instrument data collectors. Learning device used in this research is the Syllabus, Lesson Plan and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. The observation sheet was analyzed descriptive qualitative while the test of mathematics learning outcomes was analyzed statistically. Based on qualitative analysis showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic score, daily test I and daily test II are respectively 16 persons (40%), 22 persons (55%) and 27 persons (67,5%). Results of this research indicates that application of the cooperative learning type Team Games Tournament can increase mathematics learning outcomes from the students at class VIII.6 SMP Negeri 21 Pekanbaru in the second semester academic years 2015/2016.Keywords: Students Math Achievement, Cooperative Learning Type Team GamesTournament, Classroom Action Research.